Stratigraphy of deformed permian carbonate reefs in Saraburi Province, Thailand - Romana E.C. Dew (2018)
© 2018 The Author(s). Published by The Geological Society of London. All rights reserved. Kilometre-scale thrusts affect the stratigraphic order of the sedimentary rocks that form the Khao Khwang Platform in central Thailand. The effect of these thrusts requires detailed analysis to unravel the original distribution of the sedimentary units and their associated facies. The Khao Khwang Platform comprises three carbonate-dominated units identified previously as the Phu Phe, Khao Khad and Khao Khwang Formations. These carbonates are intercalated with clastic, mixed siliciclastic and carbonate sequences: the Sap Bon, Pang Asok and Nong Pong Formations. The palaeogeography of the area prior to the Indosinian Orogeny is poorly known and has herein been investigated by combining structural reconstructions, microfacies and biostratigraphy in the Saraburi area. A stratigraphic model for the Yakhtashian-Midian carbonate platform palaeogeography using the well-developed exposed sections of the Khao Khwang Platform, located in the Saraburi Province of Thailand, is presented. This has revealed the presence of several separate carbonate platforms dominated by four major Middle Permian facies (peritidal, platform interior, algal reef and basin slope), which are dated using foraminifera and algae. This model integrates recent structural studies and considers their impact on the present-day distribution of the facies in terms of platform development using biostratigraphy and detailed microfacies analysis.